Operational Management of Ro-Ro Ferry Services to Improve Crossing Service Efficiency on the Bengkalis–Sungai Pakning Route - Arwanda Arwanda; Romadhoni Romadhoni (CV. Media Digital Publikasi Indonesia, 2026)
Roll-on/Roll-off (Ro-Ro) ferry transportation plays an important role in supporting community mobility and logistics distribution in the coastal areas of Bengkalis Regency. One of the main issues on the Bengkalis–Sei. Paking route is the suboptimal efficiency of the ship's berthing time, which affects vehicle queues, departure delays, and reduces the quality of the ferry service. This study aims to analyze the efficiency of the Ro-Ro ship turnaround time on the Bengkalis–Sei. Paking route and identify the factors affecting delays in the loading and unloading process of vehicles. This research method uses a descriptive quantitative approach thru field observations, measurement of ship operational times, and statistical analysis of arrival times, unloading times, loading times, and ship departure times. The research shows that the average berthing time of the ships ranges from 38 to 52 minutes, exceeding the regional ferry port operational standard set between 30 to 45 minutes. The main factors causing inefficiency include disorganized vehicle queues, limited dock capacity, weather conditions, and suboptimal port operational coordination. Analysis shows that the implementation of a digital queue system, vehicle pattern management, and optimization of loading and unloading procedures can reduce berthing time by 15–20%. This research is expected to serve as a basis for recommendations to improve the efficiency of ferry transportation services in Bengkalis Regency.